2013
DOI: 10.4319/lo.2013.58.3.1023
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotopes reveal that chironomids occupy several trophic levels within West Greenland lakes: Implications for food web studies

Abstract: Stable isotope analyses of nitrogen (d 15 N) and carbon (d 13 C) were conducted on individual chironomid taxa from low arctic lakes to investigate the range in trophic levels covered by this diverse insect group. Five lakes were sampled, including two freshwater, two oligosaline, and one glacier influenced lake, representing the major lake types in southwest Greenland. There was a large difference in the offset of isotopic values among the different lake types. In the oligosaline lakes, we ascribe low d 13 C v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 45 publications
(113 reference statements)
1
17
0
Order By: Relevance
“…13 C values of pelagic primary production usually range from -36 to -25% (Vuorio et al, 2006;Wang et al, 2013), the range of d 13 C HC values could match well with that of the d 13 C values of phytoplankton frequently observed in CO 2 -limiting environment (Street-Perrott et al, 1997;Reuss et al, 2013). Lake Pyramid Inferior is located at 5,067 m a.s.l., and atmospheric pressure is consequently about the half of the value reported at the sea level.…”
Section: High Elevation Partial Pressure and Isotopic Fractionationmentioning
confidence: 62%
“…13 C values of pelagic primary production usually range from -36 to -25% (Vuorio et al, 2006;Wang et al, 2013), the range of d 13 C HC values could match well with that of the d 13 C values of phytoplankton frequently observed in CO 2 -limiting environment (Street-Perrott et al, 1997;Reuss et al, 2013). Lake Pyramid Inferior is located at 5,067 m a.s.l., and atmospheric pressure is consequently about the half of the value reported at the sea level.…”
Section: High Elevation Partial Pressure and Isotopic Fractionationmentioning
confidence: 62%
“…Analysis of the Chironomid trophic structure with stable isotopes showed a broad variety of feeding behaviors between taxa, suggesting that Chironomids do not belong to specific groups in the aquatic trophic web (Henriques-Oliveira et al 2003;Reuss et al 2013;Silveira et al 2013;Saito and Fonseca-Gessner 2014). Reuss et al (2013) also found that the stomach contents of Tanypodinae (e.g., Djalmabatista sp., Labrundinia sp. and Larsia sp.)…”
Section: Discussionmentioning
confidence: 99%
“…(2). Fitting was performed with non-linear regressions using the iterative Levenberg-Marquardt algorithm (Press et al 2007).…”
Section: Abiotic and Biotic Variablesmentioning
confidence: 99%
“…Trichoptera larvae had a similar trophic position but lower MMHg concentrations than Chironominae chironomids. These primary consumers may specialize on distinct types of benthic algae or detritus (Grey et al 2004;Ings et al 2010;Reuss et al 2013) that result in differential uptake of MMHg or variation in growth rate could play a role in bioaccumulation (Karimi et al 2007).…”
Section: Depth Variation In Chironomid Diet and Mmhg Concentrationsmentioning
confidence: 99%
“…Carbon and nitrogen stable isotopes are powerful ecological tracers that provide information on dietary sources or the trophic position of organisms, respectively (Fry 2006). A recent investigation (using carbon and nitrogen stable isotopes) showed striking interspecies variation in the diet of Arctic chironomids from Greenland lakes (Reuss et al 2013). At lower latitudes, delta values of carbon stable isotopes in larval chironomids are often more negative in offshore, deeper waters relative to the shoreline (Vander Zanden and Rasmussen 1999;Hershey et al 2006;Syväranta et al 2006;Jones et al 2008).…”
Section: Introductionmentioning
confidence: 97%